A Short Glimpse to the Urban Development of Tabriz during the History - NARMIN BABAZADEH ASBAGH (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Locating on North West of Iran, Tabriz, the capital of East Azerbaijan Province, is one of the important metropolises of the country. The foundation of this historic city dated back to 1500 B.C. but due to the severe earthquakes, few historic buildings remained from ancient eras. In 2012, Tabriz was selected as the most beautiful city of Iran, and it is nominated as the tourism capital of Islamic countries in 2018. Tabriz used to be the capital of Iran during different dynasties like Ilkhanid, Kara Koyunlu, Ak Koyunlu, and Safavid; it was the residence of the royal family and crown prince during the Qajar Dynasty period. Tabriz is famous as “the city of the firsts”; and the Historic Bazaar Complex of Tabriz is the biggest roofed bazaar in the world, inscribed as a World Heritage Site in 2010. Tabriz experiences the phenomenon of rapid urban growth causing the formation of slum settlements in the border zones of the city. This paper will briefly discuss the urban development of Tabriz during history. The method used in this theoretical paper is based on literature review. The aim of this paper is to improve knowledge about the urban development of Tabriz.